PERSEVERANCE AMONG UNIVERSITY STUDENTS AS AN INDICATOR OF ENTREPRENEURIAL INTENT - urban, boris; pendame, richard (South African Journal of Higher Education, 2016)
The expanding role of small businesses in the economy has generated a plethora of educational and research initiatives at HEI both locally and internationally. Despite these initiatives, in South Africa the lowest rate of entrepreneurial intentions has been recorded when compared to other sub-Saharan African countries, where students are less likely to put effort into starting their own business but rather focus their efforts into finding employment. This article investigates levels of final year university student’s entrepreneurial intentions and levels of perseverance. Perseverance influences a person’s course of action and is considered one of the key motivating factors necessary for entrepreneurship, as it acts as an inner drive towards a given goal. Following a survey, statistical analysis reveals relatively low levels of intentions and perseverance, with no links detected between the two constructs. The implications of these findings suggest that students do not hold positive perceptions of personal feasibility and desirability as far as entrepreneurship is concerned, which has a negative impact on the size of the country’s pool of intentional entrepreneurs.